2021
DOI: 10.3390/ijms222111546
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Assisted Approach for Finding Novel High Activity Agonists of Human Ectopic Olfactory Receptors

Abstract: Olfactory receptors (ORs) constitute the largest superfamily of G protein-coupled receptors (GPCRs). ORs are involved in sensing odorants as well as in other ectopic roles in non-nasal tissues. Matching of an enormous number of the olfactory stimulation repertoire to its counterpart OR through machine learning (ML) will enable understanding of olfactory system, receptor characterization, and exploitation of their therapeutic potential. In the current study, we have selected two broadly tuned ectopic human OR p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Machine learning (ML) approaches have the potential to accelerate OR deorphanization by leveraging both computational and experimental data. Although ML approaches have been widely implemented in chemosensory research, that is to predict the perception response to an odorant, ML approaches to predict OR-ligand pairs have been limited to expanding the number of ligands for ORs with known ligands, or making OR-ligand predictions without experimental validation . Other computational approaches have been applied to the identification of alternative ligands for ORs with known ligands, but not to the more difficult challenge of OR deorphanization.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning (ML) approaches have the potential to accelerate OR deorphanization by leveraging both computational and experimental data. Although ML approaches have been widely implemented in chemosensory research, that is to predict the perception response to an odorant, ML approaches to predict OR-ligand pairs have been limited to expanding the number of ligands for ORs with known ligands, or making OR-ligand predictions without experimental validation . Other computational approaches have been applied to the identification of alternative ligands for ORs with known ligands, but not to the more difficult challenge of OR deorphanization.…”
Section: Discussionmentioning
confidence: 99%
“…38 Currently, no experimental structures of human ORs are available, and homology modeling techniques have been used to rationalize the binding modes of odorant compounds into ORs and discover new OR ligands. 37,[39][40][41][42][43] AI-based methods are emerging as compelling tools to predict the 3D structure of proteins. [44][45][46] During the CASP (Critical Assessment of Structure Prediction) 14 competition, AlphaFold 2 (AF2) was shown to be able to predict the structure of protein domains at an accuracy matching experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…26-31 Despite current efforts in assigning ORs to odorant molecules, or, vice versa, in defining the chemical ligand space of individual ORs, only the molecular recognition ranges of a few ORs have been investigated. 27, 32-37…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charoenkwan et al developed a sequence-based predictor, named iBitter-Fuse, to identify bitter peptides by fusing multi-view features [ 16 ]. Jabeen et al adopted a random forest model to identify novel high activity agonists of human ectopic olfactory receptors [ 17 ]. Pouryahya et al proposed a network-based clustering method coupled with optimal mass transport theory to predict cell line-drug sensitivity, and showed that random forest modeling conducted on the resulting cell line-drug clusters outperformed alternative computational methods in predicting in vitro drug responses [ 18 ].…”
mentioning
confidence: 99%